The Role of Financial Literacy, Access to Capital, and Digital Transformation to Improve Performance of SMEs in Semi-Urban Areas - Nurfauzi, Yogi; Wafi, Inngamul; Almunawaroh, Tri; Pamuji, Slamet (PT. Riset Press International, 2026)
Micro, small, and medium enterprises (SMEs) play a crucial role in strengthening regional economic resilience, particularly in semi-urban areas where formal employment opportunities and industrial growth remain relatively limited. Despite their strategic contribution, many SMEs continue to face performance constraints due to limited financial capacity, limited access to external financing, and slow adoption of digital technologies. This study aims to examine the influence of financial literacy, access to capital, and digital transformation on SMEs performance. A quantitative explanatory approach was employed, collecting primary data through structured questionnaires distributed to 80 MSME owners in Majenang District. The research utilized Partial Least Squares Structural Equation Modeling (PLS-SEM) to analyze both measurement and structural relationships among variables. The findings reveal that financial literacy significantly improves SMEs performance by enhancing financial planning, budgeting, and decision-making abilities. Access to capital also shows a positive effect, indicating that adequate funding enables business expansion and operational stability. Furthermore, digital transformation demonstrates the strongest influence on performance, suggesting that technology adoption enhances efficiency, innovation, and market reach. The structural model explains 57% of the variance in SMEs performance, reflecting moderate predictive accuracy. These findings highlight the importance of integrated policy interventions focusing on financial education, inclusive financing, and digital capacity development to ensure sustainable MSME growth in semi-urban economies. This study contributes by providing empirical evidence on the integrated role of financial literacy, access to capital, and digital transformation in improving SME performance in semi-urban areas. The findings also highlight the need for integrated strategies in financial education, inclusive financing, and digital capacity development to support sustainable SME growth and competitiveness.